Os limites da competência do Supremo Tribunal Federal na descriminalização do aborto. - Paulino, Ezi Francisca da Silva (2019)
The purpose of this study is to analyze the role of Constitutional Courts in contemporary democracies, in order to comprehend the limits of the Federal Supreme Court's competence in decriminalizing abortion. The increasing judicialization of politics has demanded a particular and proactive attitude from the judge, legal instruments apposite to inquires of a restless society seeking for visibility. These new challenges given to the Judiciary resulted in a political participation of the judge, for who, in his eagerness to do justice, courses the path of judicial activism bringing about tension between the political system and the legal system. The Supreme Court − guardian and interpreter of the Constitution − whenever is vindicated, has showed in recent decades an extension of its function that goes beyond the interpreter and the holder who has the final say; in the increase of constitutional precepts of high semantic openness, reveals nearly a legal capacity aspect. This extremely empowered attitude from the judge arouses academic curiosities about the limits of his performance in the implement of rights. The study does not perceive the praiseworthy aspect; however, it perceives whether in making a political decision, the Supreme Court finds the theoretical field to delimit the borderline between the legislator and the judge, especially when solving a complex issue, highly charged of feelings, such as decriminalization of the abortion. Themes related to the new rights guaranteed by the democratic constitutions − equality, freedom, self-determination − involved in human dignity, are dependent on the creative power and intellectual capacity of the judge to assign a constitutional foundation in the realization of a right, especially when passiveness of the legislator occurs. The claim of constitutional visibility by social groups and movements requires a committed balanced analysis, mainly because the political choice of the legislator can be assessed by social control and reevaluated by the judge; however, the judicial right resulted by decision of the Supreme Court, which has the final say, is far from that accountability. Due to the increasing politicization of justice and the judicialization of politics, it is important to discuss the role of the constitutional judge and the limits of jurisdictional activity, when strained on the activity of legislature. Therefore, discussing about the oscillating boundary of the judge's power to interpret the Constitution or to exacerbate that power is essential. Regarding decriminalizing abortion, The STF, when compared to the Constitutional Courts and Courts involved in this study, besides justifying an anti-democratic scenario by delegation of decisionmaking powers from the political arena, shows the broadening of the judiciary's performance beyond institutional capacities, and the power dispute – even among its members − compared to the foreign courts that have decided on the subject. The voices of the streets need to be heard at the locus of constitutional legitimacy, so that it does not remain to the judge only the open parameters of the Constitution, when deciding matters of public morality and adjudicating the role of protagonist of the democratic process.